An investigation of key factors that influence employee motivation: A comparative study between male and female employees in Chinese Internet industry - Guo, Yakun (2022)
Recently, as the concept of sustainable development has been advocated, gender equality as an important issue of sustainable development has also been widely discussed. Thus, the underrepresentation of women in the Chinese Internet industry has again aroused concern. Meanwhile, the demand for high-quality talents is increasing due to the rapid development of the industry. In this context, this study aims to explore the factors that influence employee motivation in the Chinese Internet industry and to compare some differences between men and women in influencing factors to provide some insights to address the current challenges of gender equality and talent management in the Chinese Internet industry. The researcher collected data by using the questionnaire survey in the Chinese Internet industry, and received 246 valid responses. Finally, the data were processed through statistical analysis. It was found that recognition, job autonomy, and task significance have a positive and significant effect on the motivation of employees in the Chinese Internet industry. Among them, recognition, job autonomy and task significance are the key factors that influence female employees’ motivation, while recognition and task significance are the key factors that influence male employees’ motivation. What is noteworthy is that recognition is the factor that has the greatest influence on their motivation, regardless of whether they are male or female. However, in terms of the degree of influence, the influence degree of recognition on male motivation is slightly greater than that of recognition on female motivation. There is no significant difference in the influence degree of task significance on male and female motivation.